Pelatihan Sistem Informasi Sehat Holistik (SI-SEHO) untuk Pemberdayaan Kader Kesehatan - Meidiana Dwidiyanti; Sri Padma Sari; Diyan Yuli Wijayanti; Hasanah Eka Wahyu Ningsih; Reza Indra Wiguna; Akhmad Yanuar Fahmi (Holistic Nursing and Health Science, 2018)
Background: Public health services today require community empowerment so that services become affordable in every village in the community. Health cadres are existing non-professional health workers who are trained to be able to support patients or the community in addressing health problems faced. Health cadres as non-professionals who are directly dealing with the community are required to increase their ability continuously according to the changes that occur in the community.Purpose: The purpose of this study is that health cadres can improve their understanding holistically about health, through the SI-SEHO application tool so that health cadres can monitor the health of patients in the community.Method: The research used is descriptive using a qualitative approach obtained from the results of empowerment and cadre training activities using the SI-SEHO application. Data analysis is based on the objectives of the training on the use of the SI-SEHO application.Results: The results of this research activity are that health cadres can understand the meaning of health holistically that is inseparable from several dimensions of understanding holistic health. As stated by SP respondent 4 "Holistic health is comprehensive health, such as body and mind health." The ability of cadres to help individuals, families and communities increase with cadres saying "now we can help others in the community by registering through applications". Other results were obtained from research subjects as several people had been detected with physical illness and some people were detected at risk for mental disorders.Conclusion: The use of information technology is able to improve the knowledge and ability of health cadres in monitoring sick individuals or patients in the community. The development of health information systems is currently needed in the development of health services in today's digital era, such as empowering health cadres through information system training.